Effects of Synaptic Synchrony on the Neuronal Input/Output Relationship - Li, Xiaoshen (Neural Comput, 2008)
The firing rate of individual neurons depends on the firing frequency of their distributed synaptic inputs, with linear and non-linear relations subserving different computational functions. This paper explores the relationship between the degree of synchrony among excitatory synapses and the linearity of the response using detailed compartmental models of cortical pyramidal cells. Synchronous input resulted in a linear input/output releationship, while asynchronous stimulation yielded sub- and supra-proportional outputs at low and high frequencies, respectively. The dependence of input/output linearity on synchrony was sigmoidal and considerably robust with respect to dendritic location, stimulus irregularity, and alteration of active and synaptic properties. Moreover, synchrony affected firing rate differently at lower and higher input frequencies. A reduced integrate-and-fire model suggested a mechanism explaining these results based on spatio-temporal integration, with fundamental implications relating synchrony to memory encoding.